PENENTUAN KOMODITAS UNGGULAN PERTANIAN KABUPATEN OKU TIMUR - OGARI, PUTRI AYU ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The objectives of this study are (1) to know the leading subsector in agricultural sector (2) to identify potential commodities in each agriculture subsectors in Ogan Komering Ulu Timur District, (3) to determine pattern of subsectors and leading commodities of agricultural sector in Ogan Komering Ulu Timur District. Time series date are used in this study namely PDRB data based on current price (2007-2011) and agricultural commodities harvested area during range time 5 years (2008-2012). The result of analysis that food-stuff crop subsector and of plantation crop subsector represent is leading agricultural subsector in OKU Timur District. Leading agricultural commodities are cucumber, spinach, swamp cabbage, banana, chayote, chilli dan paddy. Leading plantations crops are pepper, cocoa, kapok, rubber and coconut hybrid. Growth patterns of leading subsectors and commodity in agricultural sectors in Ogan Komering Ulu Timur District comprises: Plantation and forestry subsector as grow fast subsector. While crops subsector foodstuffs included subsector advance but depressed, while Animal Husbandry and Fisheries, included subsector lagging behind. Some of leading commodities such as foodstuffs subsector consisting of corn, spinach, banana and sapodilla is a commodity advance and grow fast; while rice, sweet potato, eggplant, cucumber, squash, Duku, mango, jackfruit, rambutan and barking is a grow fast commodity; whereas peanuts, soybeans, kale, durian and mangosteen is advance but depressed commodity; cassava, green beans, string beans, chili is great, cayenne pepper, tomato, avocado and starfruit are commodities lagging behind. The leading commodities crops such as rubber and pepper plantations are advance and grow fast commodity; while coconut, cocoa, cotton and sugar included grow fast commodity; while palm oil is a commodity advance but depressed; for coffee and hazelnut included commodities lagging behind.